2016
DOI: 10.1208/s12248-016-9890-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Physiologically Based Pharmacokinetic Model to Predict Disease-Mediated Therapeutic Protein–Drug Interactions: Modulation of Multiple Cytochrome P450 Enzymes by Interleukin-6

Abstract: Abstract. Disease-mediated therapeutic protein-drug interactions have recently gained attention from regulatory agencies and pharmaceutical industries in the development of new biological products. In this study, we developed a physiologically based pharmacokinetic (PBPK) model using SimCYP to predict the impact of elevated interleukin-6 (IL-6) levels on cytochrome P450 (CYP) enzymes and the treatment effect of an anti-IL-6 monoclonal antibody, sirukumab, in patients with rheumatoid arthritis (RA). A virtual R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 37 publications
3
86
0
Order By: Relevance
“…Recently, a PBPK model involving both enzyme and drug transporter turnover has been used to predict the disposition of drugs successfully (Rasool et al, 2015;Jiang et al, 2016;Ono et al, 2017;Hsueh et al, 2018) under disease status, including diabetes or drug-drug interactions (Guo et al, 2013;Wang et al, 2013;Ono et al, 2017). The present study demonstrated that diabetes significantly altered the expression and the function of intestinal or hepatic CYP3a1, P-gp, BCRP, and OAPTs in a different manner.…”
Section: Downloaded Frommentioning
confidence: 60%
“…Recently, a PBPK model involving both enzyme and drug transporter turnover has been used to predict the disposition of drugs successfully (Rasool et al, 2015;Jiang et al, 2016;Ono et al, 2017;Hsueh et al, 2018) under disease status, including diabetes or drug-drug interactions (Guo et al, 2013;Wang et al, 2013;Ono et al, 2017). The present study demonstrated that diabetes significantly altered the expression and the function of intestinal or hepatic CYP3a1, P-gp, BCRP, and OAPTs in a different manner.…”
Section: Downloaded Frommentioning
confidence: 60%
“…Similarly, by triggering inflammation, influenza vaccination has been reported to decrease CYP activity and thus influence the systemic exposure of CYP substrates such as clozapine 168 . PBPK modeling is a powerful tool for the investigation of pharmacokinetic-based interactions between therapeutic biologics and small molecules, and has been successfully applied to quantitatively predict DDIs of CYP-modulating protein drugs (such as blinatumomab and sirukumab) and small molecule CYP substrates in patients 169 , 170 . On the other hand, pharmacokinetic interaction between two therapeutic biologics has seldom been reported.…”
Section: Drug–drug Interactionsmentioning
confidence: 99%
“…This hypothesis has been validated for TPs targeting the IL-6 pathway in patients with rheumatoid arthritis. Indeed, the mAbs tocilizumab and sarilumab, directed against the IL-6 receptor a, as well as the IL-6-neutralizing mAb sirukumab, reduce exposure of coadministrated drugs like simvastatin, midazolam, or omeprazole (Schmitt et al, 2011;Zhuang et al, 2015;Lee et al, 2017), most probably through reversal of IL-6-mediated suppression of P450 expression (Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%